PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVSDN 018 SUMBER JAYA SIAK KECIL KABUPATEN BENGKALIS - Azmie, Muhammad; Lazim N, Lazim N; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The research carried out base of the lower result of social subject in grade 4th SDN 018 Sumber Jaya Siak Kecil Kabupaten Bengkalis which is about 66.09 within minimal completeness criterion stated is 68. Among 23 students, there were only 10 students were able to achieve the score of minimal completeness criterion stated. The purpose of this research is to improve student’s achievemet on social of the fourth graders in SDN 018 Sumber Jaya Siak Kecil Kabupaten Bengkalis with the application of cooperative learning type make a match and learning model. This research was classroom action research consisting 2 cycles within 4 procedures : planning, doing, observing, and reflecting and each cycle consist of three meeting. Instruments on this research are syllabus, lesson plan, and student work sheet. Instrument for collecting data are observation sheet and test. Data which was collected were learning outcomes and teacher’s activities during lessons. After application of model of cooperative learning type make a match it was abtained student’s outcomes in UH I within average 78.26(improved from basic score 18,4%). The average score form UH II was 85.65 (improved 29,5%). Teachers activities results in the first meeting of the first cycle was 50% (fair category), and then 60% (enough category) for the second meeting in cycle I. Meanwhile in the first meeting of the second cycle was 72.5% ( good category) and then 90% (very good category) for second meeting in cycle II. Students activity in the first meeting of the cycle I was 52.5% (enough category), 62.5% (good category) for the second meeting in the cycle I. And then in the first meeting of the second cycle was 75% (good category), 92.5% (very good category) for the second meeting in cycle II. Based on the result it can be concluded that application of cooperative learning model type make a match can social in fourth graders at SDN 018 Sumber Jaya Siak Kecil Kabupaten Bengkalis.Keywords : Cooperative learning type make a match , Students Achievement the Result Of Social Lesson